Krumsabler, krutt og kanoner - Eriksen, Anne (Tidsskrift for kulturforskning, 2016)
The article goes into the history of three museums which share the history of originating from royal and princely collections of arms, military equipment and trophys. Today, the Royal Armoury in Stockholm, Deutsches Historisches Museum - Zeughaus in Berlin and Musée de l'Armée - Invalides in Paris all are modern, public museums. They are also institutions deeply stamped by the history not only of their own collections, but by that of their respective nations. Despite the inevitable differences produced by this, the article will argue that the three institutions represent a category of museums that so far has not been much explored. While recent studies in the field of museum history have brought important new understandings of cabinets of curiosity and Kunstkammer, and demonstrated the role of such collections in the Western history of knowledge, armories and trophy collections have largely been ignored. The article seeks to sketch a field for further investigations related to these collections.